2014
DOI: 10.1542/peds.2014-1543
|View full text |Cite
|
Sign up to set email alerts
|

Sofas and Infant Mortality

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Sleeping on a sofa increases the risk of sudden and unexpected infant death.WHAT THIS STUDY ADDS: Infant deaths on sofas are associated with nonsupine placement, being found in side position, surface sharing, changing sleep location, and experiencing prenatal tobacco exposure. These results may help explain why sofa sleeping is hazardous for infants. abstract OBJECTIVE: Sleeping on sofas increases the risk of sudden infant death syndrome and other sleep-related deaths. We sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 36 publications
(30 reference statements)
0
20
0
3
Order By: Relevance
“…Compared with sleeping in their own cot the risk of dying from SIDS is up to 67 times higher. A recent US study reported that deaths on sofas comprised 13% of infant sleep‐related deaths in 2004–2012 . Parents should be alerted to this risk, and counselled that it is riskier to feed an infant on a sofa, than on a bed.…”
Section: Evidence For Safe Sleeping Recommendationsmentioning
confidence: 99%
“…Compared with sleeping in their own cot the risk of dying from SIDS is up to 67 times higher. A recent US study reported that deaths on sofas comprised 13% of infant sleep‐related deaths in 2004–2012 . Parents should be alerted to this risk, and counselled that it is riskier to feed an infant on a sofa, than on a bed.…”
Section: Evidence For Safe Sleeping Recommendationsmentioning
confidence: 99%
“…The risk of SIDS in infants who co-slept on a sofa was 67 times that in infants who slept in their own cot. 43 95 Parents should be alerted to this risk and counselled that it is riskier to feed infants on a sofa than on a bed.…”
Section: What Are the Risks Of Falling Asleep With An Infant On A Sofa?mentioning
confidence: 99%
“…A recently published analysis of U.S. infant deaths on sofas found that 50.5% and 12.9% occurred on adult beds and sofas, respectively. 6 We agree that ''the issues around safe sleep are complex. No infant sleep environment is completely safe.''…”
mentioning
confidence: 99%